Teologi Perkataan: Perkataan-perkataan Yang Dicintai dan Dibenci Oleh Allah Menurut Pandangan Hamka - Murtiningsih Murtiningsih (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2018)
One of the bad habits that has developed in the community for a long time until now is talking dirty, rude, which contains utterances of hatred or the term now known as hate speech. This is due to a lack of public understanding of Islamic communication ethics that is manifested in quranic speech acts. Our Prophet Muhammad SAW said that one of the characteristics of a believer is someone who says good or just keep silent. Hamka in his interpretation gave the concept of theology of speech. Therefore, in this study, it is important to know the theology of love that God loves and hates according to Hamka. There are two things to be studied, First, what are the words that are loved by God? Second, what are some words that God hates? The method used in this study is qualitative, the type of library research, and the approach used is normative and sociological theology. While the data collection techniques used are horticulture with descriptive data analysis techniques. The purpose of this study is to find out what words are loved and hated by Allah according to Hamka. Given the culture of saying dirty and rough in Indonesia needs great attention, given that if these traits are left unchecked, it will become a disease rooted in the general public environment.